30 Years of International Climate Negotiations: Are They Still our Best Hope?. (June 2023) - Clémençon, Raymond
30 years of international climate talks have not prevented the globe from heating up more than 1 degree Celsius over post-industrial times, nor have they kept the year 2022 from breaking new temperature and extreme weather records around the world. Although the international process has been indispensable for building the foundation to move out of the carbon age, it is now time to shift attention away from the acrimonious climate talks and treat them as a sideshow, rather than the solution to the problem. An analysis of 30 years of international climate negotiations shows that multilateral climate diplomacy years ago stopped driving countries' action. National political opportunity structures, normative shifts, economic factors, and external events are what shape countries' climate policies largely independent of international climate negotiations.